COMMUNICATION THEORY: RITUAL CONSTRAINTS USED IN ENGLISH CLASSROOM INTERACTION AT TENTH GRADE STUDENTS OF SMK YADIKA LUBUK LINGGAU - Maria Ramasari (International Conference on Education and Language (ICEL), 2016)
This research aimed to investigate what are the ritual constraints used and how the ritual constraints are expressed in the English classroom interaction at the tenth grade students of SMK YADIKA Lubuklinggau. Method  applied in this study was descriptive method. The result of this research was hoped to be useful for teachers and students in teaching and learning process. It gave an input in teaching to emphasize classroom interaction effectively both enhance student achievement and more motivated students in solving the psychology problems, conceptual understanding with the result that the interaction between teacher and students are smooth and yield good feedback each other. Based on the result of data analysis there were four ritual constraints found: (a) ritual constraints in opening/ closing (b) Ritual constraints and backchannel signals, the teacher used verbal backchannel signals such as okay, yeah, and well. Beside, the students used ritual constraints and backchannel signals by using nonverbal backchannel signals such as: eyes contact and body alignment such as stand up and waving their hand. (c) Ritual constraints and turnover signals, the interaction between teacher and students gave signals by giving gaps/ small silences such as, slowing tempo, and falling intonation. (d) Ritual constraints and Grice’s maxim (relevant), the student gave signals to answer the question relevantly without any other information; and ritual constraints and Grice’s maxim (clarity), teacher demanded the students to be brief and orderly.